Salidroside Alleviates Mobocertinib-Induced Cardiotoxicity by Improving Cardiac Electrophysiology - Chi Yan; Xiaohong Liu; Xiaoyan Zhang; Pei Wei; Xuefang Li; Dongxu Li; Guhao Zhang; Meng Li; Xiayan Zang; Guangjian Lu; Fei Lin (Cardiovascular Toxicology, 2026)

Asymmetric Response of a Mesoscale Eddy Dipole to Typhoon Ma-on (2011) - Xianghai Zeng; Xiayan Lin; Yu Liu; Guoqing Han; Juncheng Xie; Han Zhang (Journal of Marine Science and Engineering, 2026)
Typhoon passages typically induce significant upper-ocean responses, especially on the right side of the typhoon track. However, how mesoscale eddies modulate this left–right asymmetry remains insufficiently understood. Using high-resolution remote sensing data and reanalysis datasets, this study examines the impacts of a mesoscale eddy dipole influenced by Typhoon Ma-on (2011). The study finds that: (1) The eddy responses exhibit significant asymmetry: during Typhoon Ma-on (2011), the amplitude, circulation speed, and radius of the left side cyclonic eddy (CE) showed anomaly increases of 8.6 cm, 4.3 cm/s, and 54.3 km, respectively, whereas those of the right-side anticyclonic eddy (AE) showed anomaly decreases of 2.9 cm, 4.8 cm/s, and 13.9 km. (2) Mesoscale eddies modulate sea surface cooling with significant left–right asymmetry, differing from the conventional pattern of stronger right-side cooling. The left side CE enhanced surface cooling by up to 2.38 °C, while the right-side AE exerted a suppressing effect, with a cooling magnitude of 0.96 °C. (3) Within the CE, a significant negative temperature anomaly develops below about 20 m. Despite a relatively high Richardson number (Ri) and weak vertical shear that suppress excessive turbulent mixing, negative Ws-driven upwelling dominates, allowing cold water to be efficiently uplifted and maintaining or intensifying surface cooling. In contrast, the AE exhibits surface cooling but persistent positive anomalies below about 40 m, reflecting the partial retention of its subsurface warm water. In this case, reduced Ri and enhanced shear instability promote stronger vertical mixing, enabling subsurface heat to be transported upward, thereby offsetting and weakening the surface cooling signal.

Interfacial charge modulation in CuFe2O4/MXene composites: Enhancing persulfate activation and efficient degradation of chloroquine phosphate - Yeqiong Huang; Zhi Song; Boxia Liu; Lin Wang; Xiayan Zhang; Jialu Liu; Dongxu Han; Chuhan Xing; Jing Zhang (Journal of Environmental Chemical Engineering, 2025)

Interinterface electron-proton co-engineering: The dual regulation of surface charge and hydroxylation promotes the efficient activation and degradation of chloroquine phosphate by monopersulfate - Zhi Song; Yeqiong Huang; Boxia Liu; Hongqiao Jiao; Yulong Ma; Lin Wang; Xiayan Zhang; Jialu Liu; Dongxu Han; Chuhan Xing; Jing Zhang (Chemical Engineering Journal, 2025)

The role of eddy merging in maintaining the quasi-permanent Ulleung Eddy - Guoqing Han; Wang Zhu; Yaofeng Wang; Xiayan Lin; Juncheng Xie; Yu Liu (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Improved identification and tracking of three-dimensional eddies in the Southern Ocean utilizing 3D-U-Res-Net - Chang Liu; Xiayan Lin; Guangjun Xu; Guoqing Han; Yu Liu (Frontiers in Marine Science, 2024)
Oceanic mesoscale eddies are prevalent throughout the global ocean, playing a critical role in material and energy transport while significantly influencing climate change. Accurate characterization of their three-dimensional structures and movement is essential for a quantitative analysis of their transport processes. Traditional eddy detection algorithms have lower successful detection rate and with more limitations, so they fall short in the complex and dynamic ocean environment. The rising trend of applying artificial intelligence (AI) algorithms, due to their efficiency, precision, and automation, addresses this challenge. This study employs the 3D-U-Res-Net algorithm to identify the three-dimensional structures of mesoscale eddies in the Southern Ocean using GLORYS12V1 data from 2011 to 2020. A vector geometry-based eddy detection algorithm (VG) initially identified 1587292 eddy snapshots in the Southern Ocean (2011–2019), which were used for training the 3D-U-Res-Net algorithm. Data from 2020 served as the ground truth and validation set. The successful detection rate of 3D-U-Res-Net algorithm is 100%, which means that it identified all 135734 eddy snapshots from the VG dataset in 2020. For eddy tracking, the VG algorithm counted 18168 eddy tracks, whereas the 3D-U-Res-Net counted 18559, reflecting a 2.15% bias. To reduce uncertainty, eddies with lifespans shorter than two weeks were excluded. The average lifespans and traveling distances for eddies detected by the 3D-U-Res-Net (VG) algorithm were 29.35 (29.61) days and 77.78 (37.60) km, respectively, with the 3D-U-Res-Net identifying eddies with longer traveling distances. The mean radius of eddies detected by the VG algorithm was 43.16 km, while the 3D-U-Res-Net detected eddies with a mean radius of 43.74 km, a 0.58 km increase. We categorized eddies into four three-dimensional structures: bowl-shaped, cone-shaped, lens-shaped, and cylindrical. The VG algorithm identified these structures in proportions of 32%, 31%, 25%, and 12%, respectively, whereas the 3D-U-Res-Net algorithm found 19.48%, 19.58%, 0.04%, and 60.9%, respectively. The 3D-U-Res-Net identified more cylindrical eddies and was approximately ten times faster than the VG algorithm. Overall, this algorithm has good performance and higher efficiency. It is an attempt of using AI for oceanic research, and more works can be carried out in the future.

Oceanic response to tropical cyclone in the northern South China Sea observed by underwater gliders during 2018 and 2020 - Yanfeng Zhang; Han Zhang; Xiaodong Tang; Shaoqiong Yang; Yanhui Wang; Xiayan Lin; Di Tian; Dake Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Detection of three-dimensional structures of oceanic eddies using artificial intelligence - Guangjun Xu; Wenhong Xie; Xiayan Lin; Yu Liu; Renlong Hang; Wenjin Sun; Dazhao Liu; Changming Dong (Ocean Modelling, 2024)

Deep learning-based forecasting model for chlorophyll-a response to tropical cyclones in the Western North Pacific - Haobin Cen; Guoqing Han; Xiayan Lin; Yu Liu; Han Zhang (Ocean Modelling, 2024)

The different dynamic influences of Typhoon Kalmaegi on two pre-existing anticyclonic ocean eddies - Yihao He; Xiayan Lin; Guoqing Han; Yu Liu; Han Zhang (Ocean Science, 2024)
Using multi-source observational data and GLORYS12V1 reanalysis data, we conduct a comparative analysis of different responses of two warm eddies, AE1 and AE2 in the northern South China Sea, to Typhoon Kalmaegi during September 2014. The findings of our research are as follows: (1) for horizontal distribution, the area and the sea surface temperature (SST) of AE1 and AE2 decrease by about 31 % (36 %) and 0.4 °C (0.6 °C). The amplitude, Rossby number (Ro = relative vorticity / Coriolis parameter) and eddy kinetic energy (EKE) of AE1 increase by 1.3 cm (5.7 %), 1.4×10-2 (20.6 %) and 107.2 cm2 s−2 (49.2 %) after the typhoon, respectively, while AE2 weakens and the amplitude, Rossby number and EKE decrease by 3.1 cm (14.6 %), 1.6×10-2 (26.2 %) and 38.5 cm2 s−2 (20.2 %), respectively. (2) In the vertical direction, AE1 demonstrates enhanced convergence, leading to an increase in temperature and a decrease in salinity above 150 m. The response below the mixed-layer depth (MLD) is particularly prominent (1.3 °C). In contrast, AE2 experiences cooling and a decrease in salinity above the MLD. Below the MLD, it exhibits a subsurface temperature drop and salinity increase due to the upwelling of cold water induced by the suction effect of the typhoon. (3) The disparity in the responses of the two warm eddies can be attributed to their different positions relative to Typhoon Kalmaegi. Under the influence of negative wind stress curl outside the maximum wind radius (Rmax) of the typhoon, triggering negative Ekman pumping velocity (EPV) and quasi-geostrophic adjustment of the eddy, the warm eddy AE1, with its center to the left of the typhoon's path, further enhances the converging sinking of the upper warm water, resulting in its intensification. On the other hand, the warm eddy AE2, situated closer to the center of the typhoon, weakens due to the cold suction caused by the strong positive wind stress curl within the typhoon's Rmax. The same polarity eddies may have different response to typhoons. The distance between eddies and typhoons, eddy intensity, and the background field need to be considered.

Variations in the Upper Ocean Heat Content of the Southern Canadian Basin - Yu Liu; Changcheng Ye; Haobin Cen; Xiayan Lin; Guoqing Han (Journal of Marine Science and Engineering, 2024)
The marine environment of the Arctic Ocean has changed rapidly in recent decades. We used reanalysis data and observational data to explore the variations in the upper ocean heat content (OHC) of the Canadian Basin (CB) and the variations in the temperature profiles of the Southern Canadian Basin (SCB). Both the reanalysis data and observational data show increasing trends for the OHC of the CB from 1993 to 2023. Compared to the World Ocean Atlas data (WOA 18/23), the reanalysis data (ORAS5 or GLORYS12V1) significantly underestimated the values of the upper OHC of the Canadian Basin. To explain the OHC differences, the Ice-Tethered Profiler (ITP) observational data were used to analyze the variations in the vertical temperature profiles. We found that the reanalysis data remarkably underestimated the maximum temperatures of the subsurface Pacific warm water and its increasing trend. Based on the short-term prediction results from the Bi-LSTM neural network, we forecasted that the upper OHC will continue to increase in the SCB, mainly due to the warming of the intermediate Atlantic warm water. The research results provide a valuable reference for assessing and improving climate-coupled models.

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

Genetic variations of CYP3A4 on the metabolism of itraconazole in vitro - Sai-li Xie; Xiayan Zhu; Nanyong Gao; Qianmeng Lin; Chaojie Chen; Yun-jun Yang; Jian-ping Cai; Guo-xin Hu; Ren-ai Xu (Food and Chemical Toxicology, 2023)

Impact of extreme climatic events on the total suspended matter concentrations in coastal waters using OceanSat-2 observations - Sravanthi Nukapothula; Ali P. Yunus; Chen Chuqun; Xiayan Lin (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Efficient degradation of tetracycline residues in pharmaceutical wastewater by Ni/Fe bimetallic atomic cluster composite catalysts with enhanced electron transfer pathway - Zhi Song; Xiayan Zhang; Boxia Liu; Jialu Liu; Lin Wang (Chemosphere, 2023)

Cross-Slope Transport by a Mesoscale Anticyclone in the Northern South China Sea - Xiayan Lin; Guixi Wang; Guoqing Han; Yu Liu; Han Zhang; Xiaomei Liao; Qiyan Ji (Journal of Marine Science and Engineering, 2023)
Cross-slope eddies play an important role in the exchange of water, salt, heat, nutrients, chlorophyll, phytoplankton and other biogeochemical elements between basin and shelf in the South China Sea. The cross-slope transport process by a mesoscale anticyclonic eddy is studied by ROMS model and satellite data. The 1000 m isobath was considered as a proxy for the slope. The anticyclone shows different features at different places on the slope: (a) the volume transport at the northeast of the slope was off-slope, while at the southwest was on-slope; (b) both on and off-slope transports were greatly enhanced during the cross-slope process, and gradually weakened after crossing the slope. The total cross-slope water transport was 5.97 Sv, which was higher than the along-slope component with −0.58 Sv. The Eulerian results also showed that enhanced cross-slope transport was related to the distance between the eddy and slope, the eddy radius, and the eccentricity of the eddy. The offline passive tracer experiment showed that particles were floating up during and after the crossing process, mainly due to the strong Ekman pumping.

Significant Wave Height Prediction in the South China Sea Based on the ConvLSTM Algorithm - Lei Han; Qiyan Ji; Xiaoyan Jia; Yu Liu; Guoqing Han; Xiayan Lin (Journal of Marine Science and Engineering, 2022)
Deep learning methods have excellent prospects for application in wave forecasting research. This study employed the convolutional LSTM (ConvLSTM) algorithm to predict the South China Sea (SCS) significant wave height (SWH). Three prediction models were established to investigate the influences of setting different parameters and using multiple training data on the forecasting effects. Compared with the SWH data from the China–France Ocean Satellite (CFOSAT), the SWH of WAVEWATCH III (WWIII) from the pacific islands ocean observing system are accurate enough to be used as training data for the ConvLSTM-based SWH prediction model. Model A was preliminarily established by only using the SWH from WWIII as the training data, and 20 sensitivity experiments were carried out to investigate the influences of different parameter settings on the forecasting effect of Model A. The experimental results showed that Model A has the best forecasting effect when using three years of training data and three hourly input data. With the same parameter settings as the best prediction performance Model A, Model B and C were also established by using more different training data. Model B used the wind shear velocity and SWH as training and input data. When making a 24-h SWH forecast, compared with Model A, the root mean square error (RMSE) of Model B is decreased by 17.6%, the correlation coefficient (CC) is increased by 2.90%, and the mean absolute percentage error (MAPE) is reduced by 12.2%. Model C used the SWH, wind shear velocity, wind and wave direction as training and input data. When making a 24-h SWH forecast, compared with Model A, the RMSE of Model C decreased by 19.0%, the CC increased by 2.65%, and the MAPE decreased by 14.8%. As the performance of the ConvLSTM-based prediction model mainly rely on the SWH training data. All the ConvLSTM-based prediction models show a greater RMSE in the nearshore area than that in the deep area of SCS and also show a greater RMSE during the period of typhoon transit than that without typhoon. Considering the wind shear velocity, wind, and wave direction also used as training data will improve the performance of SWH prediction.

Trends in Chlorophyll-a Concentration Along the Krishna–Godavari Basin as Observed From MODIS Archives - Sravanthi Nukapothula; Chuqun Chen; Ali P. Yunus; Xiayan Lin (Pure and Applied Geophysics, 2022)

Three-dimensional characteristics of mesoscale eddies simulated by a regional model in the northwestern Pacific Ocean during 2000–2008 - Guijing Yang; Xiayan Lin; Guoqing Han; Yu Liu; Gengxin Chen; Jianhui Wang (Acta Oceanologica Sinica, 2022)

Spatio-temporal analysis of east greenland polar front - Yu Liu; Jianhui Wang; Guoqing Han; Xiayan Lin; Guijing Yang; Qiyan Ji (Frontiers in Marine Science, 2022)
The East Greenland Polar Front (EGPF) is an important front with strong salinity and temperature gradients in the Nordic Seas. It is formed by the interaction between Arctic-origin and Atlantic-origin water. The variations of EGPF are closely linked with sea ice melting and heat content transport associated with North Atlantic water recirculation. For a three-dimensional (3D) daily analysis, we use the global ocean eddy resolution reanalysis product (GLORYS12V1) from 1993 to 2018 to calculate the salinity and temperature horizontal gradient in the upper ocean and obtain the spatiotemporal distribution and intensity characteristics of EGPF. After assessment, the thresholds of the salinity and temperature fronts are set to 0.04 psu/km and 0.09°C/km, respectively. Compared with satellite observations of sea ice concentration, a significant spatial relationship is observed between the main position of EGPF and the ice edge before the sea ice shrinks to the continental shelf sea area. Affected by the freshening of the Arctic-origin water due to the melting of the sea ice, the intensity and area of EGPF show significant seasonal variations. Against the background of global warming, the sea ice area presents an obvious decreasing trend in the Greenland Sea. The melting of sea ice increased annually every summer from 1998 to 2018. The heat content transport of the Atlantic-origin water has also increased in recent years. The 3D characteristics (intensity and volume) of EGPF as salinity and temperature fronts exhibit increasing trends.

Three-dimensional properties of mesoscale cyclonic warm-core and anticyclonic cold-core eddies in the South China Sea - Wenjin Sun; Yu Liu; Gengxin Chen; Wei Tan; Xiayan Lin; Yuping Guan; Changming Dong (Acta Oceanologica Sinica, 2021)